2017
DOI: 10.1021/acschembio.7b00261
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(II) Inhibits Tet-Mediated 5-Methylcytosine Oxidation by High Affinity Displacement of the Cofactor Iron(II)

Abstract: Ten-eleven translocation (Tet) family proteins are Fe(II)- and 2-oxoglutarate-dependent dioxygenases that regulate the dynamics of DNA methylation by catalyzing the oxidation of DNA 5-methylcytosine (5mC). To exert physiologically important functions, redox-active iron chelated in the catalytic center of Tet proteins directly involves the oxidation of the multiple substrates. To understand the function and interaction network of Tet dioxygenases, it is interesting to obtain high affinity and a specific inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…We found that knocking out TET2 in 786-O ccRCC cells can compromise the induction of 5hmC upon vitamin C treatment (Fig 2G). Next, we used a pan-TET inhibitor, NiCl 2 [12], to inhibit TET enzymes. However, TET2 knockout in 786-O cells did not completely block the establishment of intracellular 5hmC by vitamin C treatment, suggesting that vitamin C can also restore 5hmC catalyzed by other TET enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that knocking out TET2 in 786-O ccRCC cells can compromise the induction of 5hmC upon vitamin C treatment (Fig 2G). Next, we used a pan-TET inhibitor, NiCl 2 [12], to inhibit TET enzymes. However, TET2 knockout in 786-O cells did not completely block the establishment of intracellular 5hmC by vitamin C treatment, suggesting that vitamin C can also restore 5hmC catalyzed by other TET enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…However, TET2 knockout in 786-O cells did not completely block the establishment of intracellular 5hmC by vitamin C treatment, suggesting that vitamin C can also restore 5hmC catalyzed by other TET enzymes. Next, we used a pan-TET inhibitor, NiCl 2 [12], to inhibit TET enzymes. NiCl 2 treatment blocked vitamin C-induced 5hmC restoration in both 786-O and A498 cells ( Fig 2I).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ni has been shown to cause hypermethylation in TSGs like P53 of Chinese hamster cell line by facilitating the increased binding and activity of DNMT1 [96]. Alternatively, Yin et al showed that Ni can inhibit the activity of TET enzymes by displacing Fe(II), a possible mode of hypermethylating TSG [97].…”
Section: Heavy Metals Deregulate 5-hydroxymethylcytosinementioning
confidence: 99%
“…14 On the other hand, we found that nickel(II) inhibited Tet-mediated oxidation of 5mC to 5hmC by affinity displacement of the cofactor Fe(II) from the catalytic center of Tet dioxygenases. 15,16 Liu et al showed that arsenite, a ubiquitous environmental pollutant but also a therapeutic drug, could inhibit the catalytic activity of Tet proteins in vitro and ex vivo because of its high binding affinity toward the zinc fingers of Tet proteins. 17 The compounds with a structure similar to 2-oxoglutarate, for example, an oncometabolite 2-hydroxyglutarate and a synthetic dimethyloxalylglycine 2-oxoglutarate, can act as competitive inhibitors to reduce TET-mediated 5mC oxidation.…”
Section: ■ Introductionmentioning
confidence: 99%